All fiber passively mode locked zirconium-based erbium-doped fiber laser - Ahmad, Harith; Awang, Noor Azura; Paul, Mukul Chandra; Pal, Mrinmay; Latif, Amirah Abdul; Harun, Sulaiman Wadi (Elsevier, 2012)
All passively mode locked erbium-doped fiber laser with a zirconium host is demonstrated. The fiber laser utilizes the Non-Linear Polarization Rotation (NPR) technique with an inexpensive fiber-based Polarization Beam Splitter (PBS) as the mode-locking element. A 2 m crystalline ZirconiaYttriaAlumino-silicate fiber doped with erbium ions (ZrYAl-EDF) acts as the gain medium and generates an Amplified Spontaneous Emission (ASE) spectrum from 1500 nm to 1650 nm. The generated mode-locked pulses have a spectrum ranging from 1548 nm to more than 1605 nm, as well as a 3-dB bandwidth of 12 nm. The mode-locked pulse train has an average output power level of 17 mW with a calculated peak power of 1.24 kW and energy per pulse of approximately 730 pJ. The spectrum also exhibits a Signal-to-Noise Ratio (SNR) of 50 dB as well as a repetition rate of 23.2 MHz. The system is very stable and shows little power fluctuation, in addition to being repeatable.